Assessment of the flexural behavior of concrete block masonry beams - Haach, V. G. (2010)
This paper focus on the experimental flexural behavior of masonry beams. In the sequence of the development of a novel structural solution for reinforced masonry walls at University of Minho, different possibilities for the construction of lintels with concrete block masonry have been tested. Reinforced concrete beams with three and two hollow cell concrete blocks and with different reinforcement ratios have been built and tested in a four point loading test configuration. It was clear that horizontal bed joint reinforcement increased the ultimate flexure capacity as well as the ultimate deflection, leading to much more ductile responses. Moreover, it was also clear that a more deep analysis should be made regarding the role of the compressive strength of masonry in the parallel direction to the bed joints on the global behavior of the masonry beams.